ANALISIS SPASIAL PERGERAKAN MASSA AIR DI LAUT HALMAHERA DAN LAUT BANDA MENGGUNAKAN METODE EMPIRICAL ORTHOGONAL FUNCTION (EOF) - Fachrudy, Muhammad Adi; Munir, Rahmawati; Mandang, Idris (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2018)
The movement of water masses that occurred in the Indonesian Sea is the result of the interaction of two ocean, Pacific and Indian Ocean demonstrated by the change in salinity and temperature levels. Oceanographic research in Halmahera and Banda Sea have been carried out by analyzing changes in the level of temperature, salinity and currents on the surface of each season, West Monsoon and East Monsoon in 2010 by using Empirical Orthogonal Function (EOF). The verification of the data was done by comparing the temperature and salinity data were obtained from output of HYCOM model (Hybrid Coordinate Ocean Model) + NCODA Global 1/12 Reanalysis to observation data for 8 days in the Halmahera and Banda Sea. The results of the research showed changes in temperature and salinity that occurred in Halmahera Sea and have ranged between 28.5 ºC - 29 ºC and 34.1 psu - 34.6 psu was strongly influenced by water masses from the Pacific Ocean. The range of temperature and salinity have occurred during the West Monsoon, these water masses comes from the South Pacific moved towards Halmahera Sea brought by the New Guinea Coastal Current and that current was strong (1.06 m/s) at the time of East Monsoon took place in Indonesia. Unlike the Halmahera Sea, Banda Sea has a tendency to have temperature changes (26.9 ºC – 29.8 ºC) during the period of seasonal cycles that caused by its large region and the confluence of the water masses that come from Java Sea, Makassar Strait and affected by the temperature of Arafura Sea which has strong interaction from Indian Ocean.